Health Behaviors and Health Literacy: Questing the Role of Weak Social Ties Among Older Persons in Rural and Urban Ghana - Amoah, Padmore Adusei; Musalia, John; Abrefa Busia, Kwaku (Frontiers in Public Health, 2022)
Background: Older persons are one of the most vulnerable groups as regards low health literacy. However, little is known about the extent of limitations and multi-faceted nature of their health literacy, such as its characteristics and social and geographical dimensions. Additionally, most existing studies have predominantly treated health literacy as a risk factor of health and well-being of older persons as opposed to an outcome that must be pursued. Objectives: This study investigated the moderating role of weak social ties (bridging social capital) in the relationship between health behaviours, such as smoking, alcohol intake, voluntary body check-up and physical exercise, and health literacy among older persons in rural and urban Ghana. Methods: Data was drawn from a cross-sectional survey comprising 522 respondents across four administrative regions in Ghana. Ordinary Least Squares regression technique was used to analyse the data. Results: Older persons in urban areas had higher health literacy (Mean/Standard deviation [SD] = 9.1/4.1 vs 10.1/4.2) as well as higher bridging social capital (Mean/SD = 2.0/1.2 vs 1.6/0.9) than their rural counterparts. Bridging social capital was negatively associated with the health literacy of urban residents (B = -0.997, p< 0.01). We found evidence that smoking (B = -0.787, p< .05) and undertaking physical activities (B = 0.812, p< .01) were associated with health literacy of older persons in rural areas. Having voluntary body check-ups (B = 0.155, p<.01) was associated with health literacy in urban areas. Bridging social capital negatively moderated the association of smoking with health literacy in rural areas (B= -5.032, p<0.01), but it instead positively modified the relationship between alcohol intake and health literacy in urban areas (B= 0.185, p< 0.05). Conclusion: For policymakers and practitioners aiming to promote older persons’ health literacy as a public health asset at individual and community levels, an important starting point to achieving such goals is to understand the fundamental indicators (e.g. health behaviours) and the role that social and geographical factors play in shaping their health literacy.